The Syntax of Adjectives : A Comparative Study - Cinque, Guglielmo (Book collections on Project MUSE., 2010)
Here, Guglielmo Cinque offers cross-linguistic evidence that adjectives have two sources. Arguing against the standard view and reconsidering his own earlier analysis, Cinque proposes that adjectives enter the nominal phase either as 'adverbial' modifiers to the noun or as predicates of reduced relative clauses.